Meat processing workshop for young adults with mild mental retardation - Quitain, Leeline A. (College of Education, University of the Philippines Diliman, 2007)
A workshop was conducted in this study to determine if there is significant difference in the meat processing performance of the participants before and after the workshop and to ascertain its effectiveness in terms of instructional materials, procedure, time allotment and meat processing output. Five young adults with mild mental retardation from 15-22 years old undergone the meat processing workshop at the Maria Domenica Child Development Center. Post test and pretest scores of the participants in the tocino processing tasks were compared. Results showed a significant improvement in the meat processing skills of the participants before and after the workshop. Young adults with mild mental retardation were capable of learning culinary skills specific to meat processing; the workshop presented a viable means of vocational training for them.